The Influence of the Proinflammatory Cytokine, Osteopontin, on Autoimmune Demyelinating Disease - Chabas, Dorothée; Baranzini, Sergio E.; Mitchell, Dennis; Claude C. A. Bernard; Rittling, Susan R.; Denhardt, David T.; Sobel, Raymond A.; Lock, Christopher; Karpuj, Marcela; Pedotti, Rosetta; Heller, Renu; Oksenberg, Jorge R.; et al. (Science (American Association for the Advancement of Science), 2001)
Multiple sclerosis is a demyelinating disease, characterized by inflammation in the brain and spinal cord, possibly due to autoimmunity. Large-scale sequencing of cDNA libraries, derived from plaques dissected from brains of patients with multiple sclerosis (MS), indicated an abundance of transcripts for osteopontin (OPN). Microarray analysis of spinal cords from rats paralyzed by experimental autoimmune encephalomyelitis (EAE), a model of MS, also revealed increased OPN transcripts. Osteopontin-deficient mice were resistant to progressive EAE and had frequent remissions, and myelin-reactive T cells in OPN-/-mice produced more interleukin 10 and less interferon-γ than in OPN+/+mice. Osteopontin thus appears to regulate T helper cell-1 (TH1)-mediated demyelinating disease, and it may offer a potential target in blocking development of progressive MS.